Sociomaterial ethnography – Taking the matter seriously - Marko Niemimaa (My University, 2022)
Ethnographic research is a form of qualitative inquiry that creates deep and rich understanding of a studied naturalistic phenomenon. Traditionally, ethnographic research has focused on uncovering the meanings and interpretations of those studied. In other words, ethnographies have focused on uncovering the social construction of the world that reflects underlying interpretive stance. However, recent theoretical developments within Information Systems (IS) and management research emphasize that it is not only social constructions but 'matter' that matters. Research that aims at taking matter seriously in their theorizing are referred to as sociomateriality. Despite that empirical sociomateriality research seems to prefer ethnography as research approach, explicit reflections on the applicability of ethnography for sociomaterialist studies lack. This paper aims at contributing by arguing for the applicability of ethnography for sociomaterialist studies, building especially on agential realist worldview. Applying sociomaterial stance for ethnographies emphasize (1) studying the entanglement of social and material in lieu of social constructions; (2) sensitivity to performativity over representations; and (3) viewing researcher as part of, in lieu of, within, the phenomenon studied. The study contributes to the discussions on sociomateriality by lowering the barrier to conduct sociomaterialist empirical work. Conclusions are drawn.
MCIS 2014 Proceedings